Exchange Rate Volatility and Employment Growth: Empirical Evidence from the CEE Economies - Ansgar Belke; Ralph Setzer (Center for Economic Studies and ifo Institute (CESifo), 2003)
According to the traditional 'optimum currency area' approach, not much will be lost from a very hard peg to a currency union if there has been little reason for variations in the exchange rate. This paper takes a different approach and highlights the fact that high exchange rate volatility may as well signal high costs for labor markets. The impact of exchange rate volatility on labor markets in the CEECs is analyzed, finding that volatility vis-à-vis the euro significantly lowers employment growth. Hence, the elimination of exchange rate volatility could be considered as a substitute for a removal of employment protection legislation.
Keywords: 330; Central and Eastern Europe; currency union; euroization; exchange rate variability; job creation